DIVISOR-SUM FIBERS. Issue 2 (3rd April 2018) - Pollack, Paul; Pomerance, Carl; Thompson, Lola
Abstract : Let $s(· )$ denote the sum-of-proper-divisors function, that is, $s(n)=\sum _{d\mid n, ~d<n}d$ . Erdős, Granville, Pomerance, and Spiro conjectured that for any set $\mathscr{A}$ of asymptotic density zero, the preimage set $s^{-1}(\mathscr{A})$ also has density zero. We prove a weak form of this conjecture: if $\unicode[STIX]{x1D716}(x)$ is any function tending to $0$ as $x→ ∞$, and $\mathscr{A}$ is a set of integers of cardinality at most $x^{1/2+\unicode[STIX]{x1D716}(x)}$, then the number of integers $n\leqslant x$ with $s(n)\in \mathscr{A}$ is $o(x)$, as $x→ ∞$ . In particular, the EGPS conjecture holds for infinite sets with counting function $O(x^{1/2+\unicode[STIX]{x1D716}(x)})$ . We also disprove a hypothesis from the same paper of EGPS by showing that for any positive numbers $\unicode[STIX]{x1D6FC}$ and $\unicode[STIX]{x1D716}$, there are integers $n$ with arbitrarily many $s$ -preimages lying between $\unicode[STIX]{x1D6FC}(1-\unicode[STIX]{x1D716})n$ and $\unicode[STIX]{x1D6FC}(1+\unicode[STIX]{x1D716})n$ . Finally, we make some remarks on solutions $n$ to congruences of the form $\unicode[STIX]{x1D70E}(n)\equiv a~(\text{mod}~n)$, proposing a modification of a conjecture appearing in recent work of the first two authors. We also improve a previous upper bound for the number of solutions $n\leqslant x$, making it uniform in $a$ .